Comprehensive Organic Name Reactions and Reagents 2010
DOI: 10.1002/9780470638859.conrr691
|View full text |Cite
|
Sign up to set email alerts
|

Zemplén Deacetylation

Abstract: The efficient removal of the O ‐acetyl protecting groups of carbohydrates by treatment of the O ‐acetylated substrates in methanol with a catalytic amount of sodium methoxide at room temperature is generally known as the Zemplén deacetylation, Zemplén de‐ O ‐acetylation, or Zemplen deacetylation. In addition, after the reaction, the O ‐acetyl‐protected carbohydrates are transformed into unprotected ones, in a manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Finally, the functional group transformations and the global deprotection of the pentasaccharide 2 lead to the target molecule 1 , which is delineated in Scheme . Protected pentasaccharide 2 was subjected to a series of functional group transformations: (a) conversion of the N -phthaloyl group to an acetamido group by ethylenediamine catalyzed removal of the N -phthaloyl group followed by N - and O -acetylation using acetic anhydride and pyridine; (b) one-pot conversion of azido to the N -acetate group using thioacetic acid; (c) removal of the benzyl ether using Pd­(OH) 2 /C and H 2 ; and (d) deacetylation by NaOMe in MeOH furnished the target pentasaccharide 1 in a 64% overall yield.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, the functional group transformations and the global deprotection of the pentasaccharide 2 lead to the target molecule 1 , which is delineated in Scheme . Protected pentasaccharide 2 was subjected to a series of functional group transformations: (a) conversion of the N -phthaloyl group to an acetamido group by ethylenediamine catalyzed removal of the N -phthaloyl group followed by N - and O -acetylation using acetic anhydride and pyridine; (b) one-pot conversion of azido to the N -acetate group using thioacetic acid; (c) removal of the benzyl ether using Pd­(OH) 2 /C and H 2 ; and (d) deacetylation by NaOMe in MeOH furnished the target pentasaccharide 1 in a 64% overall yield.…”
Section: Resultssupporting
confidence: 90%
“…Formation of compound 23 was confirmed by the appearance of NMR signals at δ 5.42 (s, PhC H ), 5.82 (d, J = 3.6 Hz, 1H, H-1 B ) in the 1 H NMR and δ 101.6 (Ph C H), 97.9 (C-1 B ) in the 13 C NMR spectra. The acetate group in disaccharide 23 was selectively de-acetylated quantitatively by the Zemplén reaction to afford disaccharide acceptor 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Bipy Glu‑Ac and Bipy Gal‑Ac were then reacted with [{Ir­(F 2 ppy) 2 (μ–Cl)} 2 ] [F 2 ppy = cyclometallated anion of 2-(2,4-difluorophenyl)­pyridine] to afford mononuclear Ir Glu‑Ac ( 16 ) and Ir Gal‑Ac ( 17 ) as their chloride salts, which were purified by size-exclusion chromatography on Sephadex LH-20. Finally, deprotection under Zemplén conditionsanhydrous MeOH and catalytic NaOMeafforded the desired complexes Ir Glu ( 18 ) and Ir Gal ( 19 ). This deprotection step requires neutralization using the acidic ion-exchange resin Dowex 50W X8, and we found that leaving this step for too long resulted in the cation of the deprotected complexes Ir Glu and Ir Gal adhering to the resin, as shown by the loss of complex from solution and the appearance of green phosphorescence from the Dowex resin.…”
Section: Resultsmentioning
confidence: 99%
“…Zheng et al demonstrated that a homopolymer of 2-(diethylamino)-ethyl methacrylate prepared by Cu(0) mediated reversible deactivation radical polymerization can be modified to incorporate pendant saccharide groups. First, saccharides are modified to make them suitable alkylating agents (Scheme a) by acetylating the hydroxyl groups with acetic anhydride in the presence of iodine, reacting with one equivalent of α,ω-dibromoalkanol in trifluoroborane in diethyl ether, and then removing remaining acetyl groups via the Zemplén deacetylation (treatment in methanol with a catalytic amount of sodium methoxide). Then the saccharide alkylating agent is reacted with the polymer to quaternize the pendant amines (Scheme b).…”
Section: Synthesesmentioning
confidence: 99%